2017
DOI: 10.1002/crat.201600239
|View full text |Cite
|
Sign up to set email alerts
|

Growth of crystalline semiconductor structures on amorphous substrates for photovoltaic applications

Abstract: The growth of defined crystalline structures on amorphous materials is an almost generally difficult task. Due to the lack of a crystallographic lattice, no epitaxial intergrowth can be realized. However, for many applications the growth of crystalline layers or microstructures on such substrates, or on amorphous or nanocrystalline intermediate layers is required. For large area applications such as solar cells, glass is a particularly favored material. The article presents two studies from the field of photov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…larger crystal size. [19][20][21][22]. It is also possible to promote the rearrangement of atoms by utilizing methods like radiation [23][24][25][26][27], electric/magnetic fields [28] and heating [29].…”
Section: Introductionmentioning
confidence: 99%
“…larger crystal size. [19][20][21][22]. It is also possible to promote the rearrangement of atoms by utilizing methods like radiation [23][24][25][26][27], electric/magnetic fields [28] and heating [29].…”
Section: Introductionmentioning
confidence: 99%
“…The above approaches are an excellent proof-of-concept, but do not achieve materials savings since they all start from large continuous layers. Several bottom-up preparation strategies that reduce consumption of critical raw materials were achieved using laser nucleation and LIFT techniques, reaching PCEs of 3.4% at 20 suns 23 , 25 27 . Duchatelet et al 24 reported the fabrication of CIGSe stripes with sub-millimetre width using area-selective electrodeposition (ASED).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, whether from the view of developing basic theory or solving engineering problems, it is nessary to take a comparative study of the heteronucleation on crystalline and amorphous substrates. Although some researches paid attention to the heteronucleation on amorphous substrates [13][14][15], few work focused on the differences of heteronucleation on crystalline and amorphous materials, especially at an atomic scale. Akazawa [2] studied the deposition of ZnO on glass and sapphire c-planes, the results suggested that the crystallinity of ZnO near the glass/ZnO interface was lower than that near the sapphire/ZnO interface.…”
Section: Introductionmentioning
confidence: 99%